Prevalence of Scabies and Its Associated Risk Factors Among Cat Owners in West Nusa Tenggara, Indonesia: A Cross-Sectional Study - Aini; Halid, Musparlin; Susilo, Beny Binarto Budi (Public Health of Indonesia, 2025)
Background: Mange, a skin disease caused by the Sarcoptes scabiei mite, poses a serious threat to the health and well-being of both cats and their owners. Clinical manifestations of mange include intense pruritus, erythema, and skin rashes, which may lead to considerable discomfort and psychological distress. In urban environments with high pet density, such as Mataram City, West Nusa Tenggara, Indonesia, the risk of mange transmission increases significantly, especially through close contact with infested animals. Objective: This study aimed to identify factors associated with the incidence of mange among cat owners in Mataram City. Methods: A cross-sectional analytical study was conducted from September 2023 to February 2024 across six sub-districts of Mataram City (Ampenan, Cakranegara, Mataram, Sandubaya, Selaparang, and Sekarbela) in West Nusa Tenggara Province, Indonesia. A total of 269 cat owners were selected using a simple random sampling technique. The independent variables included demographic characteristics (age, gender), behavioral and environmental factors (handwashing practices, home hygiene, history of sharing personal items, pet grooming habits, number of pet cats, history of cat mange, and family history of scabies). Data were analyzed using descriptive statistics, Chi-square tests, and binary logistic regression with a significance level of p < 0.05 and 95% confidence interval (CI), utilizing IBM SPSS version 26. Results: Statistical analysis revealed no significant association between gender and mange infection among cat owners (p = 0.921). However, significant associations were found between mange infection and other variables, including age, handwashing practices, home environmental hygiene, sharing of personal items, pet grooming history, history of cat mange, number of pet cats, and family history of scabies (all with p < 0.001). Conclusion: The incidence of mange infection among cat owners was significantly associated with various socio-behavioral and environmental factors. These findings underscore the importance of integrated public health strategies to improve awareness, facilitate early diagnosis and treatment, and promote effective preventive measures against mange transmission. Keywords: prevalence; cat owner; Sarcoptes scabiei; scabies